Hunter in the shadows: vertebrate diet of Brown fish owl (Ketupa zeylonensis) at Satchari national park, Bangladesh - Akhter, Tania; Mithu, Atikul Islam; Naher, Habibon (Bangladesh Journal of Zoology, 2026)
Abstract not available Bangladesh J. Zool. 53(3): 411-414, 2025